(3GQJTGa GdVQH ef dSGf GdYQHs - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf,J (B745 (3g` s ((3YGeQ GdGJjGj, GdeGdcj s)
(3ChdgG (B:s
(3hHYO, aEf Yde GdfMh UYH GdeQGe, eSJYUj Ydi GdCagGe dG jfaP aj eYQaJg EdG GdPgf GdSdje s
(3BNQgG (B:s
(3JfJgj HHGH GdeaYhd GdeWdb hBNQ GdehLhO efgG bhdg(B: (3CbGFekG RjO, hbO bYO GdfGS hJbhd gfCfj GdWYGe heqQGfj Chd HGH GdeaYhd dg s
(3fSNI KGdKIs
(3JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3fSNI ofbdJ ef fSNJjf eDQNJjf aj SfI (B741(3g``` aj MjGI GdeDda hHgG fXGe GdJYbjHIs
(3HChdgG agQS ehVhYGJ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdfMhs